How to assess and manage cognitive impairment induced by treatments of non-central nervous system cancer. (December 2019) - Lange, Marie; Castel, Hélène; Le Fel, Johan; Tron, Laure; Maillet, Didier; Bernaudin, Myriam; Touzani, Omar; Perrier, Joy; Boone, Mathieu; Licaj, Idlir; Giffard, Bénédicte; Dubois, Martine; et al.
Highlights: Cognitive assessments in oncology studies depend on various methodological issues. Some batteries of electronic tests are weak in terms of psychometric development. Preclinical models have showed the impact of cancer treatments on cognition. Cognitive rehabilitation appears the most promising method of cognition management. Abstract: A number of neurotoxicity associated with oncological treatments has been reported in non-central nervous system cancers. An expert group presents the state of the art and a guide to help the choice of appropriated tools to assess patient cognition in studies on oncology and neurobehavior in animal models. In addition, current cognitive rehabilitation programs currently under evaluation are also discussed. Cognitive assessments in oncology depend on the research question, study design, cognitive domains, patients' characteristics, psychometric properties of the tests, and whether the tests are supervised or not by a neuropsychologist. Batteries of electronic tests can be proposed, but several of them are characterized by weak psychometric developments. In order to improve the comprehension on the impact of cancer treatments on cognition, new animal models are in development, and would in the future include non-human primate models. By bringing together the skills and practices of oncologists, neurologists, neuropsychologists, neuroscientists, we propose a series of specific tools and tests that accompany the cognitive management of non-CNS cancer patients.